Penggunaan Sanksi Pidana bagi Pelaku Diskriminasi Gender terhadap Pengupahan Pekerja (Analisis Undang-Undang No. 6 Tahun 2023 tentang Cipta Kerja Pasal 88) - Rohman, Aminur; Islahuddin, Muhammad (AHKAM, 2025)
Based on Article 88 of Law No. 6 of 2023 concerning Job Creation, this study examines the implementation of criminal sanctions against perpetrators of gender-based wage discrimination. Although the legislation normatively guarantees every worker’s right to a decent living and fair wages without gender discrimination, discriminatory practices manifesting as wage gaps between men and women frequently occur in practice. This research employs a normative juridical approach grounded in theories of gender discrimination, criminal sanctions, and legal certainty. The findings indicate that sanctions against wage discrimination offenders can be imposed through administrative or criminal channels. According to Article 185 of Law No. 13 of 2003 on Manpower, violations related to wages may be subject to imprisonment from one month up to four years and/or fines. Articles 88 and 88A of the Job Creation Law regulate the importance of fair wage structures and scales, as well as the government’s role in ensuring the protection of workers’ rights. Furthermore, Article 88B explicitly prohibits employers from paying lower wages to workers performing work of equal value. These policies aim to establish a transparent, fair, and discrimination-free wage system, ensuring that every worker receives a decent income in accordance with principles of justice and equality.